The Effect of Food Tree Abudance in the Home Range of Adolescent Sumatran Orangutans (Pongo abelii) in Suaq Balimbing, Gunung Leuser, National Park, South Aceh - Cinta Ningtiyas; Fitriah Basalamah; Sri Suci Utami Atmoko (Universitas Nasional Jakarta, 2026)
Ranging behavior plays a key role in the spatial and social strategies of Sumatran orangutans (Pongo abelii), a species characterized by fission-fusion dynamics and female philopatry. This study aims to analyze the relatedness between home range size and overlap levels with the utilization of food tree abundance in adolescent orangutans with differences in maternal relatedness and sex. This study uses long-term data from 2021–2024 at the Suaq Balimbing Research Station, Gunung Leuser National Park, South Aceh. Home range data were obtained using GPS, while food tree abundance was analyzed using Kriging interpolation. Home ranges were estimated using Kernel Density Estimator with a dyadic overlap approach. Statistical analysis was conducted using Generalized Linear Models to test the influence of home range size on overlap levels with related and unrelated individuals and food tree abundance. The results showed that home range overlap levels were influenced relatedness, with higher overlap is mother-offspring compared to other individuals. Adolescent orangutans will broader their space utilization in areas with low to moderate abundance of food trees. Sex and relatedness factors were more dominant in shaping adolescent ranging patterns compared to food trees. These findings indicate that the space use strategy of adolescent orangutans is not only determined by ecological factors, but also by sex and relatedness, which are more dominant in shaping adolescent ranging patterns.